Research Learning through Communication and Information Technologies inUniversity Students from Huanuco - Llanos de Tarazona, Marina Ivercia (2019)
Objective. To determine the level of research learning through communication and information technologies in university students in Huánuco. Methods. Descriptive, cross-sectional and prospective study. It was comprised of 72 students from the research course of the School of Nursing of Universidad Nacional Hermilio Valdizán in Huánuco. A questionnaire on the use of information and communication technologies, and a guide for observation of investigative skills were used - prior validation and reliability. For inferential analysis, correlation coefficient r of Pearson was used. Results. Findings revealed that students utilize ICT at a high level (81.9 %) and 88.9 % (64) presented a high level of research learning. On the other hand, a significant relationship was found between the use of ICT and research learning (with p <= 0.000). So as between. In addition, a significant relationship was found between research learning and the dimensions of ICT use such as: creativity and innovation (p <= 0.000), communication and collaboration (p <= 0.000), research and information management (p <= 0.000), critical thinking, problem solving and decision making (p <= 0.000), digital citizenship (p <= 0.000), and operation and concept of ICT (p <= 0.000). Conclusion. It exists significant relationship between the use of ICT and the research skills of students of the School of Nursing of Universidad Nacional Hermilio Valdizan in Huanuco.